Designing learning for multimodal literacy teaching viewing and representing - Lim, Fei Victor; Tan-Chia, Lydia (Routdledge studies in multimodality, 2023)
"Designing Learning for Multimodal Literacy addresses the need to design learning for multimodal literacy in a world that is increasingly saturated with print and digital media. In the current age, communication and interactions on social media are seldom made with language alone, but are often accompanied with emojis, images, and videos, making meanings multimodally. Young people, including children, are also increasingly active in making videos of themselves, their ideas and their experiences as part of their out-of-school literacy activities. In particular, for language teachers, the present shifts in our world require that teachers re-examine what they teach and how they can meaningfully and effectively teach the students in their classes today. At eight years old, Alden created his own rap music video and shared it with the world. He wrote his own lyrics and set it against the music he remixed and meshed from a music download site. Alden is in your classroom today. As his teacher, what would you teach him? How would you engage him? Alden, and children like him, is the inspiration for why the authors have written this book. The changing times and changing learners place a demand on educators to continually reflect on what and how teachers are teaching their students - to ensure that learning in school remains relevant, relatable, and would prepare them for the world of the future. Lim's book outlines how teachers can design learning for multimodal literacy. It is a result of a collaboration between an educational researcher and a curriculum developer, and offers practical resources for practitioners but also design principles and considerations based on practice with a range of students to inform and inspire academics and postgraduate students. It is poised to contribute to the global conversation and interest on how educators can reflect on the zeitgeist of the digital age and design learning for multimodal literacy"--